2018
DOI: 10.3390/molecules23123271
|View full text |Cite
|
Sign up to set email alerts
|

Combining a QSAR Approach and Structural Analysis to Derive an SAR Map of Lyn Kinase Inhibition

Abstract: Lyn kinase, a member of the Src family of protein tyrosine kinases, is mainly expressed by various hematopoietic cells, neural and adipose tissues. Abnormal Lyn kinase regulation causes various diseases such as cancers. Thus, Lyn represents, a potential target to develop new antitumor drugs. In the present study, using 176 molecules (123 training set molecules and 53 test set molecules) known by their inhibitory activities (IC50) against Lyn kinase, we constructed predictive models by linking their physico-che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…It can be concluded that VS strategies, especially Pharmacophore-based VS and combined use of VS and molecular docking, can be a reliable tool for future discovery of new KIs and have a potential to replace a HTS that is costly and time consuming process. Case Studies Application of quantitative structure-activity relationship in structure elucidation of Lyn kinase inhibitors The generalized linear model (GLM) and the artificial neural network (ANN) QSAR models were combined with structural analysis in order to define pharmacophore of Lyn kinase inhibitors (Naboulsi et al, 2018). Lyn kinase is a member of the Src family of tyrosine kinases that was found to be correlated with chemotherapeutic resistance of cancer cells in patients with CML (Chakraborty et al, 2013;Aira et al, 2018).…”
Section: Ligand-based Methods In Drug Designmentioning
confidence: 99%
“…It can be concluded that VS strategies, especially Pharmacophore-based VS and combined use of VS and molecular docking, can be a reliable tool for future discovery of new KIs and have a potential to replace a HTS that is costly and time consuming process. Case Studies Application of quantitative structure-activity relationship in structure elucidation of Lyn kinase inhibitors The generalized linear model (GLM) and the artificial neural network (ANN) QSAR models were combined with structural analysis in order to define pharmacophore of Lyn kinase inhibitors (Naboulsi et al, 2018). Lyn kinase is a member of the Src family of tyrosine kinases that was found to be correlated with chemotherapeutic resistance of cancer cells in patients with CML (Chakraborty et al, 2013;Aira et al, 2018).…”
Section: Ligand-based Methods In Drug Designmentioning
confidence: 99%
“…Several potential kinase inhibitors, such as a dual ALX/FLT3 inhibitor and a CDK9 inhibitor, were reported on the basis of LBVS methodology. 180 , 181 There are many cases of QSAR models used in the design of kinase inhibitors for VEGFR2, 182 EGFR, 183 MCL-1, 184 IKK-β, 185 , 186 LYN, 187 and MER, 188 and so on. 177 , 178 …”
Section: Advances In Efficacy Assessment Models and Technologymentioning
confidence: 99%
“…The generalized linear model (GLM) and the artificial neural network (ANN) QSAR models were combined with structural analysis in order to define pharmacophore of Lyn kinase inhibitors (Naboulsi et al, 2018). Lyn kinase is a member of the Src family of tyrosine kinases that was found to be correlated with chemotherapeutic resistance of cancer cells in patients with CML (Chakraborty et al, 2013;Aira et al, 2018).…”
Section: Application Of Quantitative Structure-activity Relationship ...mentioning
confidence: 99%